2017 IEEE Manchester PowerTech 2017
DOI: 10.1109/ptc.2017.7980987
|View full text |Cite
|
Sign up to set email alerts
|

Handling large power steps in real-time microgrid control via explicit power setpoints

Abstract: Abstract-We consider a microgrid with real-time control using explicit power-setpoints. Sudden power-steps, such as load disconnections or load in-rushes, directly affect the decisions of the microgrid controller that aims at avoiding voltage or line-ampacity violations. When trying to completely avoid these violations, the grid operation may be too restricted, which may lead to large suboptimality. However, temporary violations of the steady-state bounds are allowed by grid standards and could enable the expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 3 publications
0
14
0
Order By: Relevance
“…•} denotes the forecast of the prosumption. In this formulation, hard grid-constraints concerning nodal-voltage deviations, ampacity limits, or power factors can either be relaxed to soft constraints or be expressed via appropriate cost functions [15]. Concerning the convexity of problem (1), the cost functions of the batteries and their respective constraint sets can easily be designed to be convex.…”
Section: General Form Of the Optimization Objectivementioning
confidence: 99%
“…•} denotes the forecast of the prosumption. In this formulation, hard grid-constraints concerning nodal-voltage deviations, ampacity limits, or power factors can either be relaxed to soft constraints or be expressed via appropriate cost functions [15]. Concerning the convexity of problem (1), the cost functions of the batteries and their respective constraint sets can easily be designed to be convex.…”
Section: General Form Of the Optimization Objectivementioning
confidence: 99%
“…Recent work [29] has shown that COMMELEC performs poorly in the presence of large uncertainties, as it aims to maintain the grid bus voltages within strict ±10% bounds throughout its operation by preventing worst possible scenario. The authors in [29] introduce dynamic bounds that enable the GA to violate the voltage constraints for an interval of 500 ms, as allowed by grid standards [30]. This improves the performance of COMMELEC, allowing for optimal dispatch plan tracking, frequency support, or any other higher level functionality that the GA is performing.…”
Section: Extreme Grid Conditionsmentioning
confidence: 99%
“…is the multiplier of the voltage penalty function when the voltage is close to violation. The central idea of this patch [29] is to dynamically increase the cost of the penalty on voltage violation when the voltage is close to the allowed limits. A large value of leads the GA to return to safe voltage-region quicker.…”
Section: Extreme Grid Conditionsmentioning
confidence: 99%
“…To this end, the following property is expected to hold. This property is satisfied by a wide range of controllers including controllers using Kalman filters [12] where the state is the gain matrix, or more sophisticated controllers like [18], where the state is the time of the most recent voltage violation.…”
Section: System Modelmentioning
confidence: 99%
“…If there's only one, it is chosen, otherwise, it chooses the largest among them. (2) There is only one most common digest, and it will remain so no matter what the replicas that have yet to send digests send (lines [17][18][19]. It is chosen (as the obvious majority).…”
Section: Voting Phasementioning
confidence: 99%